Biochar Applied with Inorganic Nitrogen Improves Soil Carbon, Nitrate and Ammonium Content of a Sandy Loam Temperate Soil - Omara, Peter; Aula, Lawrence; Otim, Fred; Obia, Alfred; Bigatao Souza, Joao L. (Nitrogen, 2022)
Biochar is suggested to improve soil properties. However, its combination with inorganic nitrogen (N) fertilizer in temperate soils is not well understood. This study compared the effect of fertilizer N-biochar-combinations (NBC) and fertilizer-N (FN) on total soil N (TSN), soil organic carbon (SOC), soil nitrate (NO3 􀀀–N), and ammonium (NH4 +–N). Soil samples were taken from experiments at Efaw and Lake Carl Blackwell (LCB), Oklahoma, USA with ten treatments consisting of three N rates (50, 100, and 150 kg N ha􀀀1) and three biochar rates (5, 10, and 15 t ha􀀀1). Results at Efaw showed greater TSN and SOC under NBC compared to FN by 3 and 21%, respectively. No percentage difference was observed for NH4 +–N while NO3 􀀀–N was lower by 7%. At LCB, TSN, SOC, NO3 􀀀–N, and NH4 +–N were higher under NBC by 5, 18, 24, and 10%, respectively, compared to FN. Whereas application of biochar improved SOC at both sites, NO3 􀀀–N and NH4 +–N were only significant at LCB site with a sandy loam soil but not at Efaw with silty clay loam. Therefore, biochar applied in combination with inorganic N can improve N availability with potential to increase crop N uptake on coarse textured soils.
Keywords: biochar; total nitrogen; nitrate; ammonium; soil organic carbon